Antara Da’i dan Muballigh - Hamid, Abdul (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2024)
This research is motivated by the tendency of Indonesian Muslims to often equate the terms da’i and muballigh, even though both have fundamental differences in meaning and function within the framework of Islamic preaching. The reduction of da’wah understanding merely to sermons results in the narrowing of Islam’s da’wah role, which should be transformative. The purpose of this study is to explain the terminological distinction between da’i and muballigh based on Qur’anic sources, hadith, and da’wah literature, to elaborate on their social roles, and to demonstrate their significance for the development of da’wah studies. The research method used is a literature review by examining books, journals, and previous studies, which were then analyzed using Qur’anic Semantics and Role Theory. The data show that a da’i plays a broader role as a mentor and agent of social change, while a muballigh focuses on message delivery. In conclusion, this terminological distinction is crucial for strengthening the epistemology of da’wah and contemporary da’wah practices. Keywords: Da’i, Muballigh, Da’wah Studies, Terminology, Social Role, Islamic Communication, Epistemology of Da’wah, Social Transformation